Health-related quality of life in Brazilian patients with cutaneous leishmaniasis using EQ-5D. - Janaína de Pina Carvalho; Sarah Nascimento Silva; Tália Santana Machado de Assis; Endi Lanza Galvão; Mayra Soares Moreira; Mônica Viegas Andrade; Kenya Valéria Micaela de Souza Noronha; Gláucia Cota (PLoS ONE)
Cutaneous leishmaniasis (CL) is a neglected infectious disease with a global distribution and a known health-related quality of life (HRQoL) impact. However, no utility-based HRQoL assessments for CL patients are available. The aim of this study was to quantitatively assess the health-related quality of life among patients with CL attending a Brazilian reference center. A retrospective interview-based longitudinal study was conducted using the EQ-5D-3L/VAS to assess the current health status during active disease, and retrospectively before the onset of disease symptoms. In addition, socioeconomic data were collected via a standardized questionnaire, and sociodemographic and clinical data were collected directly from medical records. A total of 143 patients with a mean age of 52 (±17) years were included, 73% of whom were men. The mean utility score before the onset of CL symptoms was 0.858. Comparison of responses related to health status before and after disease onset revealed significant losses (p < 0.05) in all dimensions of the EQ-5D, especially those related to pain, malaise (50%) and usual activities (27%). CL also affected the median Visual Analogue Scale (VAS) score and utility score, which were 87 and 70 and 0.858 and 0.716, respectively. These results confirm the substantial negative impact of CL on all assessed dimensions of life, highlighting its role in perpetuating the cycle of suffering and poverty associated with neglected tropical diseases.